2007
DOI: 10.1137/050647621
|View full text |Cite
|
Sign up to set email alerts
|

Abstract Convexity and Augmented Lagrangians

Abstract: The ultimate goal of this paper is to demonstrate that abstract convexity provides a natural language and a suitable framework for the examination of zero duality gap properties and exact multipliers of augmented Lagrangians. We study augmented Lagrangians in a very general setting and formulate the main definitions and facts describing the augmented Lagrangian theory in terms of abstract convexity tools. We illustrate our duality scheme with an application to stochastic semi-infinite optimization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…Proof Given the perturbation function φ of f , define the marginal function h as in (15). Thus, the Fenchel-Moreau conjugate of the marginal function h is given by h * :…”
Section: Lemma 3 the Dual Of Scmmentioning
confidence: 99%
See 2 more Smart Citations
“…Proof Given the perturbation function φ of f , define the marginal function h as in (15). Thus, the Fenchel-Moreau conjugate of the marginal function h is given by h * :…”
Section: Lemma 3 the Dual Of Scmmentioning
confidence: 99%
“…In this section, we apply the general duality scheme, that can be found in [10,15,18], in the setting of SCM problems with a particular choice for the coupling function. Without any loss of generality, we can redefine f considering, in addition, f (x) = +∞ when x / ∈ X , and, equivalently, rewrite the SCM problem (5) as…”
Section: The Duality Schemementioning
confidence: 99%
See 1 more Smart Citation
“…The following additional assumption on σ is often used in the context of augmented Lagrangians [11,20].…”
Section: Equality Constrained Problemsmentioning
confidence: 99%
“…Indeed, it has been shown that for a certain family of augmented Lagrangians, both zero duality gap and saddle point properties hold [18,Chapter 11]. These duality properties have been extended to more general kinds of Lagrangians and more general frameworks (including infinite dimensional spaces) [11,13,17,19,20]. Many solution techniques for nonconvex optimization rely on the good duality properties of augmented Lagrangians [2,3,4,5,6,7,8,9,14].…”
Section: Introductionmentioning
confidence: 99%